Towards a Hybrid Conceptual Operational Management Model of Cañazo Supply Chain: A Research on the Sugar-Cane Spirit from Peru - Arturo Imberti; Edgar D. Ramos; Kelsey Provost; Anshuman Neil Basu (International Journal of Supply Chain Management, 2020)
The present research seeks to show the importance of applying process management techniques and food safety norms in the operational processes of the supply chain to know the meaning and the need for an integrated hybrid model. The article reviews the sugarcane distillery sector of Peru and its main operational problems. Based on the literature reviewed and discussed with academics who have knowledge of the food supply chain, an integrated hybrid model was developed to help any distillery with lower levels of competitiveness than its competitors in other sectors, such as pisco, applying techniques of process management and food safety to increase the efficiency of liquor distilleries. The findings confirm that distilleries can increase their efficiency, thanks to the higher performance of their operations after their alignment with the integrated model.